EFEKTIVITAS MACAM PESTISIDA NABATI DAN PUPUK ORGANIK PADAT UNTUK MENGENDALIKAN SERANGAN ORGANISME PENGGANGGU TANAMAN PADA TANAMAN PADI - Dian Eka Kusumawati; Istiqomah Istiqomah; Driska Arnanto (BUANA SAINS, 2022)
It is important to take wise and appropriate actions in responding to the presence of plant-disturbing organisms in cultivated plants, especially rice plants. Farmers often use chemical pesticides to combat pests. They often use these pesticides excessively without regard for the pest to trying control, which may have unfavorable effects such as degrading the quality of the environment and endangering human and animal health. Organic farming practices have recently become more common in the agricultural industry. Organic agricultural goods that only use natural ingredients as fertilizers and insecticides are starting to replace agricultural products that used to use chemical fertilizers and pesticides. Using pesticides carelessly and inappropriately can harm your health, the environment, and the ecological balance. The aim of this research is to find out the types of botanical pesticides and solid organic fertilizers that are effective in controlling rice plant pests and as an effort to increase production. In this research used two variables were used in a factorial randomized block design. Neem leaves, soursop leaves, and papaya leaves are some examples of the many forms of botanical insecticides. Solid organic fertilizer is the second aspect (cow, goat, and chicken manure). The collected findings show that treatment with a mixture of chicken manure and vegetable insecticides from neem leaves showed the best effect in reducing the percentage of pest attacks on rice plants. In addition, it can improve plant development to increase the productivity of rice plants.